Interleukin-12 in infectious diseases. - Romani, L (1997)
Interleukin-12 (IL-12) is a potent immunoregulatory cytokine that is crucially involved in a wide range of infectious diseases. In several experimental models of bacterial, parasitic, viral, and fungal infection, endogenous IL-12 is required for early control of infection and for generation and perhaps maintenance of acquired protective immunity, directed by T helper type 1 (Th1) cells and mediated by phagocytes. Although the relative roles of IL-12 and gamma interferon in Th1-cell priming may be to a significant extent pathogen dependent, common to most infections is that IL-12 regulates the magnitude of the gamma interferon response at the initiation of infection, thus potentiating natural resistance, favoring Th1-cell development; and inhibiting Th2 responses. Treatment of animals with IL-12, either alone or as a vaccine adjuvant, has been shown to prevent disease by many of the same infectious agents, by stimulating innate resistance or promoting specific reactivity. Although IL-12 may enhance protective memory responses in vaccination or in combination with antimicrobial chemotherapy, it is yet unclear whether exogenous IL-12 can alter established responses in humans. Continued investigation into the possible application of IL-12 therapy to human infections is warranted by the role of the cytokine in inflammation, immunopathology, and autoimmunity.